THE EFFECTS OF INTERNET, MEDIA, ADVERTISEMENT ON DEVELOPMENT OF LANGUAGES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article discusses about the impact of technology globalization and media on languages. It explores the benefits of it and it’s effective sides for using any kind of language. The author presents arguments supporting benefits of globalization and its impact on language. Additionally, the article acknowledges potential challenges and offers suggestions for overcoming them. Overall, it advocates for the significance of the effect that made technology and media on language.